Financial Performance Analysis at Politeknik Kesehatan Kendari as Work Unit of Non-Tax State Revenue Towards Public Service Agency - Rochmad Munandar; Andi Ratna Sari Dewi; Pratiwi Febrianti (International Journal of Business and Quality Research, 2023)
This study aims to measure and present the financial performance of the Politeknik Kesehatan Kendari as a NTSR Satker to a Public Service Agency work unit.A Cash Ratio of 0% gets a score of 0 out of a maximum score of 3. Thus the Cash Ratio gets a score of 0 in the Bad category (C). The current ratio of 511.92% gets a score of 3.6 out of a maximum score of 4.8. Thus the current ratio gets a score of 80 in the Good category (A). Receivables Collection Period 7 days, gets a score of 4.5 out of a maximum score of 4.5, thus getting a score of 100 in the good category (AAA). Fixed Asset Turnover Ratio of 12.66 with a score of 0.6 out of a maximum score of 1.5 with a score of 80 in the Moderate category (B). Return on Fixed Assets of Negative 38.96 gets a score of 0 out of a maximum score of 1.5, So the Return on Fixed Assets is 0 with a Bad category (C). Equity Return is Negative 38.66, getting a score of 0 out of a maximum score of 1.5, So the Equity Return Value is 0 with the Bad category (C). The ratio of NTSR Revenue to Operational Costs of 26.47% gets a score of 0.9 out of a maximum score of 3, so that the Ratio of NTSR Revenue to Operational Expenses ratio gets a score of 30 in the Bad category (CC). Overall the Performance Assessment from Financial Ratio analysis at the Politeknik Kesehatan Kendari got a score of 9.6 out of a maximum score of 19,5, so that it got a score of 49 in the moderate category (BB). Referring to No. 129/PMK.05/2020 pasal 7 Politeknik Kesehatan Kendari a healthy financial performance by category MEDIUM (BB), so that it can be considered to become a PSA work unit.